Terminal sedation and the “imminence condition” - Cellarius, V. (Journal of medical ethics, 2008)
“Terminal sedation” refers to the use of sedation as palliation in dying patients with a terminal diagnosis. Although terminal sedation has received widespread legal and ethical justification, the practice remains ethically contentious, particularly as some hold that it foreseeably hastens death. It has been proposed that empirical studies show that terminal sedation does not hasten death, or that even if it may hasten death it does not do so in a foreseeable way. Nonetheless, it is clear that providing terminal sedation in combination with the withholding or withdrawing of life-prolonging treatments such as fluid and nutrition can foreseeably hasten death significantly—what is here called early terminal sedation (ETS). There are ethical justifications for the use of sedation in palliative care and thus it would seem that ETS is an ethically and legally acceptable practice. However, what emerges from the literature is the repeated assertion that terminal sedation must be restricted to use in imminently dying patients—the “imminence condition”—and that therefore ETS is unacceptable. This restriction has taken on greater significance with the trend of palliative care to include the care of patients who are not imminently dying. This paper proposes to show that although there is widespread intuitive support for the imminence condition, it does not follow from the justifications for sedation as palliation, and that explicit arguments for the imminence condition are needed.